Retrospective and prospective evaluation of the Amplicor HPV test for detectionof 13 high-risk human papillomavirus genotypes on 862 clinical samples - Poljak, Mario (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Background: Persistent infection with a subgroup of at least 15 high-risk human papillomavirus (HPV) genotypes is considered as a necessary although insufficient etiological factor in the development of cervical carcinoma. As aconsequence, HPV testing has recently become an important part of the cervical carcinoma screening and detection algorithms. Aim of the study: To evaluate the analytical performance of a recently developed polymerase chain reaction (PCR)-based Amplicor HPV test (Roche Molecular Systems) in comparisonwith the Hybrid Capture 2 HPV DNA test (hc2) (Digene Corporation) for the detection of 13 high-risk HPV genotypes. Inhouse consensus PGMY09/PGMY11 and CPI/Ilg PCRs targeting two different HPV genes coupled with HPV genotyping were used as an HPV internal reference standard. Materials and methods: In the retrospective evaluation, 550 cervical scrape specimens with previously established HPV status were included. Additionally, 312 cervical scrape specimens were tested prospectively for the presence of 13 high-risk HPV genotypes by both hc2 and Amplicor HPV test. Results: In the retrospectiveevaluation, the Amplicor HPV test results agreed almost completely with the HPV internal reference standard results. In the prospective evaluation performed on 312 samples, the concordant Amplicor and hc2 results were obtained in 85.9% of samples tested. Conclusion: In our hands, the Amplicor HPV test demonstrated high analytical sensitivity and specificity. The higher analytical specificity of Amplicor in comparison to that of hc2 can be considered clinically useful. Prospective studies with clinical endpoints are urgently needed to assess the clinical utility of the higher analytical sensitivity of the Amplicor HPV test for primary HPV screening and triaging patients with ASC-US.
Keywords: Cervix Neoplasms; Classification; diagnostika; Etiology; Genotip; Genotype; infekcije; Isolation And Purification; maternični vrat; Maternični vrat, novotvorbe; Papillomavirus, Human; papiloma virusi; Papilomavirus človeški; Polimerazna, verižna reakcija; Polymerase Chain Reaction